2006
DOI: 10.1007/s00106-005-1260-z
|View full text |Cite
|
Sign up to set email alerts
|

Kochleaimplantation bei Kindern im 1. Lebensjahr

Abstract: In order to achieve an optimal timing for the development of speech understanding, cochlear implantation should be performed before the age of 2 years. This study revealed no additional risks for children in Gr. 1, but the development of speech understanding was better. As a consequence, cochlear implantation should be considered for very young children with an identified bilateral profound hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 27 publications
1
11
0
5
Order By: Relevance
“…Holman et al [2013] found over 60% of correct scores of their youngest implanted children at the 12-month follow-up. Similarly, Lesinski-Schiedat et al [2005] found over 70% correct answers at several subsets of the MAIS scores on their youngest group of implanted patients (<12 months) at the 1-year follow-up. In both studies, at 21 months of age [Holman et al, 2013] and 24 months of follow-up [Lesinski-Schiedat et al, 2005], scores of both age groups varied between 80 and 100% correct scores, without differences with respect to age at CI being identified between groups.…”
Section: Speech Production Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Holman et al [2013] found over 60% of correct scores of their youngest implanted children at the 12-month follow-up. Similarly, Lesinski-Schiedat et al [2005] found over 70% correct answers at several subsets of the MAIS scores on their youngest group of implanted patients (<12 months) at the 1-year follow-up. In both studies, at 21 months of age [Holman et al, 2013] and 24 months of follow-up [Lesinski-Schiedat et al, 2005], scores of both age groups varied between 80 and 100% correct scores, without differences with respect to age at CI being identified between groups.…”
Section: Speech Production Outcomesmentioning
confidence: 99%
“…The best available evidence is based on independent subjective outcome measures and indicates that implantation before the age of 2 is beneficial when considering speech perception (on combined PB-K and CNC but not on GASP scores) [Leigh et al, 2013;Dunn et al, 2014;Lesinski-Schiedat et al, 2005]. Implantation before 12 months resulted in better speech production (DEAP and IT-MAIS) [Ching et al, 2013;Leigh et al, 2013], auditory performance (CAP-II score) [Colletti et al, 2012] and two out of the five receptive language scores (combined PLS-4 and OWLS and PPVT scores) [Colletti et al, 2012;Leigh et al, 2013;Holman et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Umso wichtiger ist es daher, das geschä-digte Ohr z. B. durch Hörhilfen zu verbessern [1,2,13]. In jüngster Zeit wird ein neuer Ansatz erforscht: das Ersetzten geschädigter oder abgestorbener Haarzellen durch Stammzellen.…”
Section: Stammzelltransplantation In Die Kochlea Originalienunclassified